Mechanism study on improving chloropicrin fumigation effect by covering fumigated soil with appropriate thickness film - Chunyan Dai; Chunyan Dai; Minghua Li; Minghua Li; Rongfeng Pu; Rongfeng Pu; Yameng Lin; Yameng Lin; Hualin Liu; Hualin Liu; Yuan Liu; Yuan Liu; et al. (Frontiers in Microbiology)
IntroductionPanax notoginseng, a perennial medicinal plant, suffers from severe continuous cropping obstacles. Chloropicrin (CP) as a soil fumigant can be used to effectively mitigate continuous cropping obstacles. Mulch film application plays a crucial role in enhancing the effectiveness of CP soil fumigation. However, the effects of mulch film application on soil microorganisms and quality of P. notoginseng, as well as underlying mechanisms, are unclear.MethodsTo investigate the effect of cover thickness on fumigation efficacy following CP treatment, this study compared soil temperature, humidity, CP residue, microbial diversity, and crop parameters under soil covered with films of 0.06 mm (6S) and 0.08 mm (8S) thickness after CP fumigation.Results and discussionThe 6S film showed less degradation, higher transparency, tensile strength, and elongation at break than 8S. Soil temperature (ST) was lower, and soil water content (SWC) higher under 6S mulch film application with CP fumigation (F6S) compared to 8S (F8S). On the 14th day of fumigation, the CP content of F6S treatment was 28.97% higher than that of F8S treatment. F6S increased beneficial microbial phyla and genera such as Bacillus, Sphingomonas, and Mortierella, and reduced harmful Fusarium and Nectriaceae more effectively than F8S. Beneficial bacteria OTUs were significantly correlated with mulch thickness (MT), ST, and SWC. In addition, the F6S maintained the rhizosphere microbial diversity balance and inhibited the accumulation of pathogens (Ilyonectria and Fusarium), leading to a high seedling survival rate. The above changes further promoted the accumulation of biomass and saponins in P. notoginseng. Overall, F6S treatment improved fumigation efficacy and the yield and quality of P. notoginseng, making it a strategic solution to regenerate the soil health, quality, and production of functional root crops facing continuous cropping obstacles.